Предмет: Математика,
автор: vadimurut91
Выполните задание, плачу 60 баллов.
Приложения:
Ответы
Автор ответа:
0
Ответ:
Пошаговое объяснение:
(a+2)/(2a-a²)-(a+6)/(4-a²)=(a+2)/(a(2-a))-(a+6)/((2-a)(2+a))=
((2+a)(a+2)-(a+6)a)/(a(2-a)(2+a))=(2a+4+a²+2a-a²-6a)/(a(2-a)(2+a))=
(4-2a)/(a(2-a)(2+a))=(2(2-a))/(a(2-a)(2+a))=2/(a(2+a))
Похожие вопросы
Предмет: Немецкий язык,
автор: ЕкатеринаВеликая753
Предмет: Русский язык,
автор: gricenko01
Предмет: Русский язык,
автор: знатока
Предмет: Русский язык,
автор: Linativi